Praktik Digital Marketing Melalui Sosial Media dan Identitas Visual sebagai Alat untuk Mengembangkan UMKM - Darmawan, Moh. Faridl; Widyaningsih, Bekti; Zulmi, Rizal; Riswamanda, Alfito; Utami, Sri; Pratama, Leonita Yogi; Cahyanti, Lutfiyah Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
This community service is carried out to handle the marketing process of MSMEs. Because in Kromong Village it is still focused offline, namely relying on markets around the business location to market its products. Apart from that, we are still focused on using word of mouth marketing techniques for promotional media. The aim is to gain new knowledge, understanding and skills in marketing for the business they run so that they can help increase sales of MSMEs in Kromong Village. There are many forms of digital marketing that can be done, one of which is through social media, social media marketing or social media marketing. This is to build awareness, recognition and action for your brand, business, product or anything else. The method for implementing this activity is community service with a Participatory Action Research (PAR) approach oriented towards community empowerment. Because empowerment must always meet the needs and solve problems that exist in society. The results of this activity were carried out in the form of direct assistance so that researchers could freely share knowledge with partners, and partners could also ask confusing related questions directly so that partners' understanding could be deeper. Apart from that, mentoring. This practice is carried out directly so that researchers can coordinate directly with partners regarding important and necessary matters relating to these MSMEs